Innovative cluster approach to teaching computer science and information technology in the general secondary education system - Azimkulov Saykhun Niyozaliyevich (Zien Journals, 2021)
Work based on the cluster approach provides opportunities for the formation of a regional pedagogical (educational) cluster. Approaches to the formation of the concept of pedagogical (educational) cluster development, the main stages of its formation are described. Mechanisms of interaction of participants of cluster integration, pedagogical (educational) cluster development management system are presented.
Keywords: cluster integration of educational institutions; cluster approach; ystem of management of pedagogical; cluster participants in the framework of cluster integration